Reduction of lung inflammation, oxidative stress and apoptosis by the PDE4 inhibitor roflumilast in experimental model of acute lung injury - Kosutova, P; Mikolka, P; Kolomaznik, M; Balentova, S; Adamkov, M; Calkovska, A; Mokra, D (Physiological research, 2018)
Damage of alveolar-capillary barrier, inflammation, oxidative injury, and lung cell apoptosis represent the key features of acute lung injury (ALI). This study evaluated if selective phosphodiesterase (PDE)-4 inhibitor roflumilast can reduce the mentioned changes in lavage-induced model of ALI. Rabbits with ALI were divided into 2 groups: ALI without therapy (A group) and ALI treated with roflumilast i.v. (1 mg/kg; A+R group). One group of healthy animals without ALI served as ventilated controls (C group). All animals were oxygen-ventilated for further 4 h. At the end of experiment, total and differential counts of cells in bronchoalveolar lavage fluid (BALF) and total and differential counts of white blood cells were estimated. Lung edema formation was assessed from determination of protein content in BALF. Pro-inflammatory cytokines (TNFalpha, IL-6 and IL-8) and markers of oxidation (3-nitrotyrosine, thiobarbituric-acid reactive substances) were detected in the lung tissue and plasma. Apoptosis of lung cells was investigated immunohistochemically. Treatment with roflumilast reduced leak of cells, particularly of neutrophils, into the lung, decreased concentrations of cytokines and oxidative products in the lung and plasma, and reduced lung cell apoptosis and edema formation. Concluding, PDE4 inhibitor roflumilast showed potent anti-inflammatory actions in this model of ALI.
Keywords: Animals; bronchoalveolární lavážní tekutina; Rabbits; apoptóza; Bronchoalveolar Lavage Fluid; Female; Pneumonia; oxidační stres; pneumonie; Apoptosis; ženské pohlaví; Aminopyridines; inhibitory fosfodiesterasy 4; Oxidative Stress; Phosphodiesterase 4 Inhibitors; cyklopropany; Benzamides; Male; modely nemocí na zvířatech; benzamidy; Disease Models, Animal; Cyclopropanes; králíci; zvířata; mužské pohlaví; Acute Lung Injury; akutní poškození plic; aminopyridiny